Two-Parametric Immunological Score Development for Assessing Renal Involvement and Disease Activity in Systemic Lupus Erythematosus - Christopher Sjӧwall; Chelsea Bentow; Mary Ann Aure; Michael Mahler (Journal of Immunology Research)
Objective. Anti-double-stranded (ds) DNA and anti-C1q autoantibodies are useful tools in the assessment of disease activity and nephritis in systemic lupus erythematosus (SLE) patients. This study aimed to explore the utility of these antibodies along with anti-Ku antibodies in an oligoparametric model approach for the assessment of disease activity and lupus nephritis. Methods. Samples from 261 well-characterized SLE patients were tested using chemiluminescent immunoassays (CIA) for anti-dsDNA and anti-Ku antibodies as well as by anti-C1q antibody ELISA (Inova Diagnostics, USA). Of these SLE patients, 26.4% had lupus nephritis (LN) at the time of blood draw or had a history of LN, and modified SLE disease activity index-2K (SLEDAI) scores were used to assess disease activity. Results. All three antibodies demonstrated higher prevalence and higher antibody levels in active versus inactive SLE patients and in LN versus non-LN patients. When oligoparametric analysis was performed, the likelihood of LN and patients with active disease increased with dual and triple positivity. Conclusions. Anti-dsDNA and anti-C1q antibodies are useful tools to identify disease activity and/or renal involvement in SLE patients. In addition, the combination of those antibodies in a two-parametric score might improve the clinical utility of those markers.